PREDIKSI MASSA PROPPANT, VOLUME INJEKSI, DAN WAKTU INJEKSI FLUIDA PEREKAH PADA OPERASI HYDRAULIC FRACTURING UNTUK SUMUR PANAS BUMI - Arif Wicaksono, Reza
Indonesia is located in the Ring of Fire region so that there are a lot of active volcanoes in Indonesia. This condition makes Indonesia has a great geothermal energy prospect, but not all of it can be produced. One of the geothermal energy systems that has not been produced is hot dry rock system. Hot dry rock system has not been produced because the rock does not contain any fluid and it has low permeability. However, the rock has a high temperature so that it has a great heat content. One method to produce this system is to do hydraulic fracturing, which is to create a fracture in the rock using a fracturing fluid. After the fracture is formed, proppant is injected to keep the fracture from being closed then the water is injected through the fracture so that the steam will be produced and it will be flowed through the production well. In the geothermal industry the fracture is made not only for flowing fluid but also as a medium for transferring heat between the injected water and the rock. The system of utilizing geothermal energy with this method is known as engineered geothermal system. This study discusses how to determine the proppant mass needed to keep the fracture from being closed, determine the injection volume of fracturing fluid needed, and determine the injection time needed to create the fracture based on the physical properties of the rock that will be fractured, the size of the fracture that will be created, and also the type of proppant and fracturing fluid that will be used. In addition, the sensitivity is also done in this study to determine the most influential physical property in determining the proppant mass, the injection volume, and the injection time needed. The calculation results for making fracture in this study show that it takes 662,897.07 lbm of proppant and 1,317.26 bbl of fracturing fluid with 32.93 minutes of injection time. The sensitivity graph shows that the fracture length has the greatest influence in determining proppant mass and fracturing fluid injection volume while the fluid injection rate has the greatest influence on the length of fracturing fluid injection time.